Assessing the nutrient intake and diet quality of adults wearing dentures using the healthy eating index - Grace Gomez Felix Gomez; Huiping Xu; Lisa A. Spence; Parul Patel; Vanlianpar Bualteng; Biju Cheriyan; Daniel O. Clark; Nana Adwoa Gletsu-Miller; Thankam P. Thyvalikakath (BMC Oral Health)
Abstract Background Diet quality might be impacted among individuals after receiving their dentures. This study assessed nutrient intake and diet quality among adults wearing maxillary and/or mandibular complete dentures using 24-hour dietary recalls and compared with the dietary reference intakes recommended for healthy individuals. Methods An observational clinical study was conducted with adult participants aged ≥ 50 years wearing maxillary and/or mandibular complete denture/s. They completed two 24-hour dietary recalls, first at an in-person visit and the second within seven days via phone using the Automated Self-Administered (ASA24®) 24-hour web-based platform. Diet quality for each participant was measured as Healthy Eating Index (HEI) scores ranging from 0 to 100 based on 13 food components. HEI is classified as (1) “poor” (< 51); (2) “needs improvement” (51–80); (3) “good” (> 80) diet quality. Descriptive statistics included participant characteristics, nutrient intake, and diet quality. The Macro and micronutrient intakes of the study participants were compared with the estimated average requirements and adequate intake values. Multivariable regression methods determined the association between the diet quality and participant characteristics. Furthermore, Spearman Correlation was used to estimate the associations between diet quality, macro, and micronutrient intake. Results A total of 93 participants participated in the study. 57% were female, 50% were black, 54% wore maxillary and mandibular dentures, 43% received dentures between 50 and 59 years, and 51% wore dentures for more than 10 years. The average HEI score was 54 (sd = 11.9), with a need for diet improvement among 59% of the participants. None of the participants had a good diet quality. More than 90% of the participants consumed dietary fiber, vitamin D, vitamin E, and choline below nutrient recommendations. Study participants with poor diet quality had significantly lower daily intake of fiber, magnesium, potassium, and vitamins A, D, C, B-6, and K (p < 0.05). Conclusion The diet of the denture-wearing study participants was inadequate. Routine monitoring of the quality of dietary intake of individuals wearing dentures must be incorporated into a dental clinician’s workflow. Further studies must be conducted to evaluate the diet quality of individuals undergoing prosthodontic treatment plans. Based on evidence-based research findings, interdisciplinary care approaches to promote continuity of care among denture wearers need to be established. Clinical trial number Not applicable.